Phosphorus Flame Retardants for Polymeric Materials from Gallic Acid and Other Naturally Occurring Multihydroxybenzoic Acids. (24th December 2018) - Howell, Bob A.; Oberdorfer, Kendahl L.; Ostrander, Eric A.
Abstract : The development of polymer and polymer additives from renewable biosources is becoming increasingly prominent. This reflects increasing concerns about sustainability, environmental quality, and human health. Bioproducts produced in nature are generally inexpensive and benign in the environment. Moreover, degradation of derivatives does not yield toxic products. Gallic acid (3, 4, 5-trihydroxybenzoic acid) is found widely in nature and has long been touted for its medicinal qualities. 3, 5-Dihydroxybenzoic acid is also produced by several plants, most notably buckwheat. Both compounds, as the anilide and methyl ester, respectively, have been converted to a series of phosphorus esters, both phosphonate and phosphate. Esters have been fully characterized using spectroscopic and thermal methods. These compounds display good flame retardancy at low loadings in DGEBA epoxy resin.